Penerapan Model Fishbowl untuk Meningkatkan Kerjasama Tim - Respati Puji Wiyati; Siti Nurhayati; Sri Supadmi; Puji Hastuti; Mauria Tania; Nurul Chotimah (KAMPUS AKADEMIK PUBLISING, 2026)
Student collaboration is a crucial element in learning to develop intelligence, exchange ideas, and encourage active participation. The Fishbowl learning model is effective in fostering these skills. This study aims to describe the steps, advantages, and disadvantages of applying the Fishbowl model in learning at Madrasah Aliyah Negeri Temanggung, Madrasah Tsanawiyah Negeri 3 Karanganyar, Madrasah Aliyah Negeri Sukoharjo, and Madrasah Aliyah Negeri 2 Rembang. Using a descriptive qualitative approach, the subjects were teachers as informants, with data collection techniques including interviews, observation, and documentation. The results show that the Fishbowl steps include dividing the group into discussion and listening groups, forming a semicircle like a fishbowl, allowing listeners to join in, and facilitating teachers' opinions and questions. The advantages are: encouraging critical thinking, free expression, collaborative idea contribution, and mature solution selection. The disadvantages are: deviation of answers, domination of active students, long time for teachers with less classroom experience, and intensity of implementation. Conclusion: The Fishbowl model can be applied to improve student teamwork in madrasahs.